Effects of Planting Time and Spacing on the Growth and Yield of Carrot Under Dry Land Condition at Bina, Mymensingh (Research in Agriculture Livestock and Fisheries, 2020)
An experiment was conducted at the Horticulture Farm of the Bangladesh Institute of Nuclear Agriculture (BINA), Mymensingh, Bangladesh during the period from November, 2018 to April, 2019 to study the effects of planting time and spacing on the growth and yield of carrots under dry land condition at BINA, Mymensingh. Five different planting times viz. November 10, November 20, November 30, December 10 and December 20 and four different spacing’s of 25× 20 cm, 20× 20 cm, 15× 15 cm and 10× 10 cm were used . This experiment was laid out in randomized complete block design with three replications. Planting time showed significant effects on the growth and yield of carrot in respect of plant height, number of leaves, fresh and dry weights of leaves and roots, length ad diameter of roots, gross and marketable yields of carrot. The highest marketable yields (39.70 t/ha) was obtained from November 20 planting, whereas the lowest yields (25.02 t/ha) from December 20 planting. Plant spacing also significantly influenced on all the mentioned parameters. The highest marketable yields (34.95 t/ha) was observed from the closest spacing of 10× 10 cm. In respect of combined effect, November 20 planting with the closest spacing of 10× 10 cm produced significantly the highest marketable (42.29 t/ha) yields of carrot.Res. Agric., Livest. Fish.7(3): 373-382,  December 2020